Psikoedukasi untuk Meningkatkan Perkembangan Psikososial Anak dalam Pencegahan Kekerasan Seksual pada Siswa SDN 3 Tanjung Lago - M. Farhan Alghifari; Desy Arisandy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service program aimed to provide psychosocial education for children in the prevention of sexual violence at SD Negeri 5 Tanjung Lago. The methods used included audiovisual media in the form of short educational films related to sexual abuse prevention, presentation slides to clarify the material, and role-play simulations that reflected real-life situations to train children on how to respond when facing unsafe or unwanted situations. The results showed that children’s initial understanding of sexual violence prevention was relatively low. However, the implementation of the psychoeducational program through a combination of instructional materials, role play, and educational videos proved effective in improving children’s knowledge and self-protection skills.